High-performance inverted PThTPTI:PC71BM solar cells. (July 2015) - Li, Hui; Cao, Jiamin; Zhou, Qing; Ding, Liming; Wang, Jizheng
Abstract: A highly efficient D–A conjugated polymer (PThTPTI) was applied in inverted organic solar cells. Optimized PThTPTI:PC71 BM cells give an outstanding PCE as high as 9.20%, with V oc of 0.882 V, J sc of 14.31 mA/cm 2, FF of 72.9%, and over 72% EQE in the range of 420–640 nm. DIO (1, 8-diiodooctane) effects on device performance are also systematically investigated. The result shows that the addition of DIO produces greatly improved nanoscale morphology of the blend film, which actually does not lead to significantly improved light absorption and build-in potential. Instead it leads to more efficient charge transfer, less carrier recombination, longer effective carrier lifetime and higher carrier mobility, which are the main contributors for the high efficiency. Graphical abstract: Highlights: TPTI as a promising polycyclic acceptor unit for developing high-performance D–A polymers is explored. Inverted PThTPTI:PC71 BM solar cells display an outstanding PCE as high as 9.20%. DIO effects on device performance are systematically investigated.